1974
DOI: 10.1287/trsc.8.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Finding All Shortest Paths

Abstract: We present a procedure for finding the shortest routes between all pathconnected ordered pairs of nodes in a network. Furthermore, our approach is quite simple and highly efficient for a special class of network problems. In particular, this class of networks subsumes a number that appear in real world applications. For instance, the Polish government and the Texas Water Resources Developmental Board have developed water resource analysis models that are in this class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Special decomposition algorithms have been proposed for shortest-path problems on large-scale sparse networks [2,[8][9][10]12,14,17,19,22]. In most of these algorithms shortest paths are obtained between a source node and all the other nodes or between every pair of nodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Special decomposition algorithms have been proposed for shortest-path problems on large-scale sparse networks [2,[8][9][10]12,14,17,19,22]. In most of these algorithms shortest paths are obtained between a source node and all the other nodes or between every pair of nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, he indicated that star-shaped networks and linear networks are two subclasses of tree-structured networks. Glover, Klingman, and Napier [8] suggested a decomposition procedure which also takes advantage of the linear structure of a network. However, the procedure may sometimes produce very few subnetworks or even no decomposition at all.…”
Section: Introductionmentioning
confidence: 99%